Eating behavior in the time of COVID-19 pandemic case study of selected young professionals in Metro Manila - Dela Paz, Janine Severino; Bantang, Joanne R.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Is there a change in the eating behavior of Filipinos during the COVID-19 pandemic? This case study aimed to describe the eating behavior of Filipino young professionals before and during the COVID-19 pandemic alert levels situation in terms of meal planning, eating practices, and eating-related problems. Moreover, it also aims to identify the factors that influence the change in their eating behavior. A total of 20 Filipino young professionals, residing in Metro Manila, were purposively selected for the survey and in-depth interview. The gathered data were analyzed through content analysis and descriptive statistics. Results showed that the pandemic played a significant role in changing eating behavior. Changes in family dynamics and responsibilities have caused a ripple effect in eating behavior within households. Young professionals tend to prepare their own meals which are sometimes unhealthy and based only according to their cravings. Moreover, price and convenience appeared to be the most important factors for young professionals prompting them to utilize technology for online purchases and transactions. In terms of eating practices, many young professionals shifted towards healthier eating behaviors, particularly during the peak of the pandemic, when they have more time for meal preparation. Unfortunately, it was temporary as the mode of work returned to face-to-face set-up and majority of them reverted to their usual habits, such as consuming processed meals. It is important to note that although the respondents have knowledge about the importance of consuming healthy meals, this knowledge does not always translate into practice. It is thus, recommended that while seminars, training, and programs about healthy eating behavior, menu planning and consumption must continue, a simultaneous value clarification and behavior modification strategies or intervention must also be in place. A collaborative work among relevant government agencies, home economists, and related experts assessing impact of programs and policies related to healthy eating behavior is also warranted.
Thesis (Master of Home Economics) -- University of the Philippines Diliman
Bibliography: pages 114-128.
Keywords: Food preferences -- Philippines -- Metro Manila; COVID-19 Pandemic, 2020- -- Philippines -- Metro Manila